Research Evaluation of Financial Research – Evidence from a Survey - Enrico Miersch (Credit and Capital Markets – Kredit und Kapital, 2020)
I explore the role of team collaboration in financial research based on a survey of conference participants. Precisely, I investigate whether various team and project characteristics are associated with research quality. The use of different quality proxies, i.?e., normalized total citations, Journal Impact Factor, and publication success in top 10 finance journals, and the origin of the data allow me to not only analyse working papers spread throughout the entire quality spectrum but also to research new variables, e.?g., team work quality and communication intensity. I document a positive relation between research quality and the following project characteristics: authors' scholarly capability, working paper's presentation at top tier conferences and research seminar series.
Keywords: G00; 330; Research Quality; Assessment of Research Quality; Survey; Citation Analysis; Research Collaboration